Pediatric Nursing, Psychiatric and Surgical Issues - Ozdemir, Oner (IntechOpen, 2015)
The book is not a classic pediatric text book. It shows different approaches to some pediatric topics. Our aim in this book, as understood from its title, is to describe some specific issues related to nursing, psychiatric and surgical issues. The book Pediatric Nursing, Psychiatric and Surgical Issues has 8 chapters which are placed in 4 different sections, to enlighten patients and pediatricians on current developments on specific pediatric issues.